2008
DOI: 10.1097/prs.0b013e31817d5476
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Processed Lipoaspirate Cells: Influence of Donor Site on Cell Concentration

Abstract: The lower abdomen and the inner thigh may have higher processed lipoaspirate cell concentrations. These sites may turn out to be better sources of adult mesenchymal stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(90 citation statements)
references
References 25 publications
4
67
1
12
Order By: Relevance
“…Although reports in the literature (Padoin et al, 2008) suggest the lower abdomen and inner thighs to be richer in the source of stem cells, this study used C-Kit expression as a proxy measurement for stem cells. C-Kit expression also measures lymphocytes and on this basis the conclusions of this paper are in question.…”
Section: Fat Harvestingmentioning
confidence: 99%
“…Although reports in the literature (Padoin et al, 2008) suggest the lower abdomen and inner thighs to be richer in the source of stem cells, this study used C-Kit expression as a proxy measurement for stem cells. C-Kit expression also measures lymphocytes and on this basis the conclusions of this paper are in question.…”
Section: Fat Harvestingmentioning
confidence: 99%
“…Regardless of, whether there is an optimal donor site, experts suggest, that some sites may be preferable to others. Some studies have shown that lower abdominal fat contains more stem cells compared to other areas [45]. Fat survival can depend on the count of stem cells, which support the graft through adipogenesis and angiogenesis [46,47].…”
Section: Cd3mentioning
confidence: 99%
“…Tissue engineering (TE) has looked for the combined use of regenerative cells, matrices or cell carriers, and growth factors (GF) 1,[22][23][24][25][26][27][28][29][30][31][32][33] . There are some controversial evidences showing lack in cranial vault reconstructions when ADSCs are used 34,35 .…”
mentioning
confidence: 99%